Measurements and ecological implications of non‐rainfall water in desert ecosystems—A review. Issue 6 (19th July 2019) - Kidron, Giora J.; Starinsky, Abraham
Abstract: The current review focuses on the contribution of non‐rainfall water (NRW) to arid and semiarid regions (with a focus on the Negev), where NRW may provide a constant source of water that may facilitate the survival of different organisms, especially microorganisms. Factors that determine the amounts of NRW and the contribution of NRW to plants and organisms are discussed. Nevertheless, although important, significant variation exists regarding the amounts of NRW, which may stem from improper use or inherent drawbacks of some of the measurement devices. This may lead to erroneous conclusions regarding the possible role played by NRW. For instance, with prokaryotes (bacteria and cyanobacteria) requiring liquid water (≥0.1 mm) for growth, small inaccuracies in NRW around this threshold may either lead to the conclusion that NRW is sufficiently high to facilitate their growth, or rather, is too low to facilitate their growth. Arguing that some of the devices used to measure NRW may greatly overestimate the amounts, the possible contribution of NRW to soil bacteria and cyanobacterial biocrusts is analysed. We suggest that although NRW may assist the growth and survival of mosses and some types of lichens (mostly non‐crustose), no conclusive findings were thus far reported regarding the use of dew for cyanobacteria growth. The use of dew by cyanobacterial crust for growth should be critically examined, and the possibility that NRW may even result in a negative carbon balance for cyanobacterial crusts should be considered.